Program Sosialisasi dan Penyuluhan Hukum tentang Pencegahan Narkoba Menuju Pendidikan Berkualitas di Lingkungan UPT SMP Negeri 1 Kampa melalui Program Kerja Mahasiswa KUKERTA MBKM Desa Sawah Baru - Ramdani, Fikry; Azzahra, Cindy; Maharani, Maharani; Tampubolon, Veronica Allysia; Caesar, Muhammad Aisar Akmal; Marbun, Andreas; Bahira, Awra Nela; Xega, Xega; Ramadhani, Siti Hawa; Arafah, Arafah; Pandiangan, Hanna Rida Yolavani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The 2025 Community Service Program (KUKERTA) under the Merdeka Belajar Kampus Merdeka (MBKM) initiative at the University of Riau was implemented in Sawah Baru Village, Kampa Subdistrict, Kampar Regency, with the aim of supporting Sustainable Development Goal (SDG) 4 on quality education. Although Sawah Baru Village has considerable human potential, awareness of the dangers of narcotics remains limited, posing high risk particularly among school-aged children. Adopting a participatory approach, the students conducted a drug prevention outreach program among the pupils, using lecture presentations, interactive question-and-answer discussions, and poster distribution as supporting media. Evaluation results revealed increased student participation and enhanced understanding of types of narcotics, their harmful impacts, and methods to resist negative environmental influences. The activity proved effective in improving students’ knowledge and awareness. Sustaining this effort requires collaboration among teachers, parents, and relevant authorities to foster a healthy, drug-free school environment. This program also can serve as a model for developing community-based educational ecosystems within schools.